2019
DOI: 10.3390/tropicalmed4020070
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Brucella Seroprevalence in Peri-Urban Dairy Farms in Five Indian Cities

Abstract: Brucellosis is endemic among dairy animals in India, contributing to production losses and posing a health risk to people, especially farmers and others in close contact with dairy animals or their products. Growing urban populations demand increased milk supplies, resulting in intensifying dairy production at the peri-urban fringe. Peri-urban dairying is under-studied but has implications for disease transmission, both positive and negative. In this cross-sectional study, five Indian cities were selected to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
1
15
2
2
Order By: Relevance
“…For Brucella spp., our study found a seroprevalence of 14% in Odisha (95% CI 10-19%), and 6% in Assam (95% CI 4-10%), higher than observations previously made of 5% seroprevalence among sheep and goats in Odisha [15], and a 2% seroprevalence recorded in goats in Assam [38]. Previous studies have however shown particularly high prevalence (70% herd prevalence) in cows in peri-urban Guwahati, the capital of Assam [39].…”
Section: Discussioncontrasting
confidence: 76%
“…For Brucella spp., our study found a seroprevalence of 14% in Odisha (95% CI 10-19%), and 6% in Assam (95% CI 4-10%), higher than observations previously made of 5% seroprevalence among sheep and goats in Odisha [15], and a 2% seroprevalence recorded in goats in Assam [38]. Previous studies have however shown particularly high prevalence (70% herd prevalence) in cows in peri-urban Guwahati, the capital of Assam [39].…”
Section: Discussioncontrasting
confidence: 76%
“…It provides immunogenic protection and supplies nutrients, such as proteins, fat, carbohydrates, vitamins, and minerals, in an easily digestible form than any other single food [1]. There has been an increase in milk consumption in the developing countries, including India and the trend is likely to continue as the demand for animal-source food has shown a rising trend due to population growth, changing lifestyles, increasing wealth, and increasing dependence of large vegetarian population on dairy products for proteins and other micronutrients [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of milk traders in Guwahati, along with low productivity in dairy farms and low knowledge among all dairy value chain actors, has been observed in earlier studies as well ( 12 , 14 ). The difference between Guwahati and the other cities has also been demonstrated when it comes to disease prevalence ( 15 ).…”
Section: Discussionmentioning
confidence: 93%